2012
DOI: 10.3791/3958
|View full text |Cite
|
Sign up to set email alerts
|

Endothelialized Microfluidics for Studying Microvascular Interactions in Hematologic Diseases

Abstract: Advances in microfabrication techniques have enabled the production of inexpensive and reproducible microfluidic systems for conducting biological and biochemical experiments at the micro-and nanoscales 1,2 . In addition, microfluidics have also been specifically used to quantitatively analyze hematologic and microvascular processes, because of their ability to easily control the dynamic fluidic environment and biological conditions [3][4][5][6] . As such, researchers have more recently used microfluidic syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 16 publications
(3 reference statements)
0
43
0
Order By: Relevance
“…In addition, we observed that glucocorticoid and catecholamine-mediated leukocyte demargination occurs in more physiologic microfluidic devices cultured with a confluent endothelial monolayer that spans the entire inner surface area of the device, providing further evidence that this demargination effect likely also occurs in vivo (Fig. S3) (25).…”
Section: In Vitro Treatment Of Isolated Human Leukocytes With Glucocomentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, we observed that glucocorticoid and catecholamine-mediated leukocyte demargination occurs in more physiologic microfluidic devices cultured with a confluent endothelial monolayer that spans the entire inner surface area of the device, providing further evidence that this demargination effect likely also occurs in vivo (Fig. S3) (25).…”
Section: In Vitro Treatment Of Isolated Human Leukocytes With Glucocomentioning
confidence: 66%
“…A custom-written MATLAB code (MathWorks) extracted individual leukocyte positions from the series of confocal images. For endothelialized experiments, devices were endothelialized as previously described (25). For the capillary bed experiments, isolated granulocytes in PBS (1-3 × 10 6 cells per milliliter) were perfused through a microfluidic model of a capillary bed (23) at 0.250-1 μL/min.…”
Section: Methodsmentioning
confidence: 99%
“…Some advanced microfluidic systems, such as reconstruction of lung-on-chip model demonstrated that this technology is capable to reproduce complex integrated organ-level responses to bacteria and inflammatory cytokines involving microvascular channels 25,26 . The most widely used material for microfluidic applications is PDMS, as it is an optically transparent, nontoxic, and gas permeable soft elastomer 2729 . Various hydrogel devices, or hydrogel/PDMS hybrid devices have also been used to promote cell adhesion, or serve as a physical barrier to induce chemical gradient 21,3032 .…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has shown that vascular phenomenon relevant to hematologic processes can be studied in vitro by culturing endothelial cells to a confluent monolayer in microchannels. 13,14 These "endothelial-ized" microfluidics allow us to recapitulate the in vivo endothelium-bloodFeCl 3 interface and monitor the status of the endothelium during FeCl 3 application, while controlling the flow conditions and cellular and molecular "inputs" to the system. We find that all isolated blood components and molecules aggregate in a FeCl 3 concentration-dependent manner, with and without endothelial cells.…”
Section: Introductionmentioning
confidence: 99%